Is it the time to study air pollution effects under environmental conditions? A case study to support the shift of in vitro toxicology from the bench to the field. (September 2018) - Gualtieri, Maurizio; Grollino, Maria Giuseppa; Consales, Claudia; Costabile, Francesca; Manigrasso, Maurizio; Avino, Pasquale; Aufderheide, Michaela; Cordelli, Eugenia; Di Liberto, Luca; Petralia, Ettore; Raschellà, Giuseppe; Stracquadanio, Milena; et al.
Abstract: Air pollution and particulate matter are recognised cause of increased disease incidence in exposed population. The toxicological processes underlying air pollution associated effects have been investigated by in vivo and/or in vitro experimentation. The latter is usually performed by exposing cells cultured under submerged condition to particulate matter concentration quite far from environmental exposure expected in humans. Here we report for the first time the feasibility of a direct exposure of air liquid interface cultured cells to environmental concentration of particulate matter. Inflammatory proteins release was analysed in cell medium while differential expression of selected genes was analysed in cells. Significant association of anti-oxidant genes was observed with secondary and aged aerosol, while cytochrome activation with primary and PAHs enriched ultrafine particles. The results obtained clearly show the opportunity to move from the lab bench to the field for properly understanding the toxicological effects also of ultrafine particles on selected in vitro models. Graphical abstract: Image 1 Highlights: An exposure methodology for environmental exposure is presented. PM environmental doses of exposure cause biological responses in BEAS-2B. Correlation of HO1 gene with secondary aerosol is reported. Secondary and aged PM determine oxidative responses in cells. Primary PM rich in PAHs increase CYP1B1 expression.